Pengaruh work life balance terhadap job satisfaction dimediasi oleh affective commitment - Erinda Dwimagistri Sukmana; Miftah Faridl (Psychological Journal: Science and Practice, 2022)
This study aims to determine the effect of work-life balance on job satisfaction by mediating affective commitment. This research was conducted on employees at service companies. The subjects of this study were 101 people who were examined and selected as samples. Data collection in this study used a work-life balance scale, generic job satisfaction scale, and affective commitment scale. The analysis technique used is linear regression technique and PROCESSby Hayes. The mediation model shows that work life balance has an effect on affective commitment (a = 0.628, p < 0.000) and affective commitment has an effect on job satisfaction (b = 0.459, p< 0.000). Path c shows a signiﬁcant effect between work-life balance and job satisfaction (=0.494, p < 0.000). while path c’ shows (=0.288, p < 0.000) which means that affective commitment mediates the effect of work-life balance on job satisfaction with partial mediation.